ESRA19-0406 Pain relief after shoulder surgery – what happens when the block wears off?. (30th August 2019) - Mcivor, C; Mitchell, J; Ramsey, J
Abstract : Background and aims: Brachial plexus blockade is an effective form of analgesia for shoulder surgery. Once the nerve block subsides the management of pain becomes a major challenge for anaesthetists. A standard for best practice suggests that 100% of patients should be satisfied with their pain management plan. Methods: Patient's consented prior to surgery for a follow up telephone call 2–4 days post-operatively. It was agreed that formal ethics approval was not required and all data was anonymised. Detailed pain scores and analgesia requirements were explored on the follow up. Results: 30 patients identified, 8 lost to follow-up. The average blocks duration was 25.84 hours. 27% of patients reported severe pain at rest with 45% experiencing severe pain during movement. 36% of patients felt they did not have sufficient analgesia once discharged home. 8 out of 22 felt they needed stronger pain relief. All but 1 patient stated that they would have a repeat nerve block. Once the nerve block wore off it was clear that a large number of patients had inadequate analgesia. Despite the introduction of oxycodone to supplement analgesia, and a patient information leaflet to give advice on pain relief, patients often did not take analgesia as prescribed. Conclusions: Single injection brachial plexus blocks are limited to a time span shorter than the duration of moderate to severe post-operative pain. The gold standard technique is continuous interscalene blocks (CISB) albeit technically challenging. Future work should concentrate on overcoming the barriers to CISB and aim to increase its uptake.